Articulação entre questões étnicas e raciais e a Educação de Pessoas Jovens e Adultas em propostas pedagógicas difundidas pelo site do Ministério da Educação - Correia, Rosimara Silva (2013)
The current research, named Articulation among ethnical and racial issues and the Adults and Young Adults Education in Pedagogical Proposals widespread by the Education Ministry website , unleashed from the personal motivations and bibliographical and exploratory research, was dedicated to identify and analyze in the Pedagogical Proposals published on the Education Ministry website by the Continuous Education Secretary, Literacy, Diversity and Inclusion proposed to the Adults and Young Adults Education elements to education of the ethnical and racial relationship and identify in the Pedagogical Proposal presented in the book Guidelines and Actions for the Education of the Ethnical-Racial Relationship , published on the Education Ministry website by the Continuous Education Secretary, Literacy, Diversity and Inclusion proposed to the Adults and Young Adults Education. From these objectives, the research was guided by the following questions: in the Pedagogical Proposals, published on the Education Ministry website, about Adults and Young Adults Education, what is the role of the ethnical and racial issues? And in the book Guidelines and Actions for the Education of the Ethnical-Racial Relationship what is the role of the Adults and Young Adults Education? Is there an effective dialogue between them? To answer this question the studies were based on the analyze research of quantitative and qualitative content proposed by Bardin. For the qualitative analyzes, realized in the Pedagogical Proposal for the Adults and Young Adults Education a semantic field was created with the radicals: cult , differenc , discrimin , diversit , ethn , identi , prejudice , blac , and racism and an analytical frame was synthesized and for the quantitative analyzes realized in the book Guidelines and Actions for the Education of the Ethnical-Racial Relationship we pointed out all of the indications and recommendations to implement the law 10.639/03 in the modalities of Childhood Education, Elementary Education, High School, Adults and Young Adults Education, Licentiate and Quilombola Education and we synthesized in a comparative frame. About the results, in the Curricular Proposals for the First and Second Segment, the Ethnical and racial themes are approached in a transversal way with emphasis on the areas of Society and History studies and, in the Pedagogical Proposal for Education of Ethnical and Racial Relations, the Adults and Young Adults Education occupies one of the least prominent roles related to the suggestion of activities for the effectiveness of the law 10.639/03. Therefore, these two axles do not have an effective dialogue between each other.